Rumen and fecal microbiota profiles associated with immunity of young and adult goats - Luo, Tao; Li, Yongtao; Zhang, Wenying; Liu, Jianxin; Shi, Hengbo (Frontiers in immunology, 2022)
Low immunity at birth increases risk of disease of young livestock, such as goat kids. Microbiomes change as animals mature, and a healthy microbiome is related to decreased risk of disease. The relationship between microbiota profiles and immunity at different developmental stages remains unclear. Young (female, n = 12, 30 d) and adult (female, n = 12, 2 yrs. old) Saanen dairy goats were used to investigate changes in rumen microbiomes, fecal microbiomes, and their correlations to circulating immune factors. Serum IgG ( P = 0.02) and IgM ( P < 0.01) were higher at 2 years than 30 d of age, but there were no differences in IgA ( P = 0.34), IL-2 ( P = 0.05), IL-4 ( P = 0.37) and IL-6 ( P = 0.73) between ages. Amplicon sequencing analysis revealed young goats had a higher diversity of bacterial communities in rumen and lower diversity in feces compared with adult goats. Ten genera in rumen and 14 genera in feces were positively correlated with serum IgM concentration across both ages. Olsenella , Methanosphaera, Quinella , Candidatus_Saccharimonas , and Methanobrevibacte r in rumen and Ruminobacter , Treponema , Rikenelaceae_ RC9_ gut_ Group in feces were positively correlated with the concentration of IgG. The correlation analysis using weighted gene co-expression network analysis showed the MEblue module was positively associated with the IgG and IgM. These data provide novel insight into the association between rumen-feces microbiota and immune response. Further experiments are needed to investigate whether inoculating young livestock with immune-related bacteria identified can improve the immune status. Our data suggest a possible strategy to improve the immunity of the kids by alterative microbiota profiles.